Tinjauan Fikih Taharah terhadap Penyandang Disabilitas (Studi Buku Fikih Penguatan Penyandang Disabilitas): Review of Taharah Jurisprudence for Persons with Disabilities (Book Study of Jurisprudence Strengthening Persons with Disabilities) - Radhiah Tulhidayah; Ahmad Syaripudin (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This research aims to determine the views of taharah jurisprudence towards people with disabilities who are blind and physically disabled in the book Fiqh Strengthening Persons with Disabilities. The problems raised in this research are; First, what is the concept of taharah for people with disabilities in the book Fiqh, Strengthening People with Disabilities. Second, what is the review of taharah jurisprudence towards people with disabilities in the book Jurisprudence for Strengthening Persons with Disabilities. This type of research is library research, with qualitative descriptive methods. The results of this research are mentioned in the book Fiqh on Strengthening Persons with Disabilities, namely; First, the concept of taharah for people with disabilities, if conditions make it impossible for them to purify themselves, then they can ask for help/assistance. In this case, people with visual impairments (blind) are assisted in the issue of water impurity and may make ijtihad regarding vessels. As for people with physical disabilities (note the body), when performing purification only the mahram can help. However, if there is no one to help him then he still has to complete his wudu when performing prayers according to his ability. Second, the review of taharah jurisprudence towards people with disabilities is the same as for sick people, because ḍawu al-'ażar (people who are elderly) have their own laws regarding this matter.